Photocatalytic Hydrogen Production using Polymeric Carbon Nitride with a Hydrogenase and a Bioinspired Synthetic Ni Catalyst1. Issue 43 (9th September 2014) - Caputo, Christine A.; Gross, Manuela A.; Lau, Vincent W.; Cavazza, Christine; Lotsch, Bettina V.; Reisner, Erwin
Abstract Solar‐light‐driven H2 production in water with a [NiFeSe]‐hydrogenase (H2ase) and a bioinspired synthetic nickel catalyst (NiP) in combination with a heptazine carbon nitride polymer, melon (CNx), is reported. The semibiological and purely synthetic systems show catalytic activity during solar light irradiation with turnover numbers (TONs) of more than 50 000 mol H2 (mol H2ase)−1 and approximately 155 mol H2 (mol NiP)−1 in redox‐mediator‐free aqueous solution at pH 6 and 4.5, respectively. Both systems maintained a reduced photoactivity under UV‐free solar light irradiation (λ>420 nm).